Association between the melatonin receptor 1B gene polymorphism on the risk of type 2 diabetes, impaired glucose regulation: a meta-analysis. - Qing Xia; Zi-Xian Chen; Yi-Chao Wang; Yu-Shui Ma; Feng Zhang; Wu Che; Da Fu; Xiao-Feng Wang (PLoS ONE, 2012)
BACKGROUND: Melatonin receptor 1B (MTNR1B) belongs to the seven-transmembrane G protein-coupled receptor superfamily involved in insulin secretion, which has attracted considerable attention as a candidate gene for type 2 diabetes (T2D) since it was first identified as a loci associated with fasting plasma glucose level through genome wide association approach. The relationship between MTNR1B and T2D has been reported in various ethnic groups. The aim of this study was to consolidate and summarize published data on the potential of MTNR1B polymorphisms in T2D risk prediction. METHODS: PubMed, EMBASE, ISI web of science and the CNKI databases were systematically searched to identify relevant studies. Odds ratios (ORs) and 95% confidence intervals (95% CIs) were calculated. Heterogeneity and publication bias were also tested. RESULTS: A total of 23 studies involving 172,963 subjects for two common polymorphisms (rs10830963, rs1387153) on MTNR1B were included. An overall random effects per-allele OR of 1.05 (95% CI: 1.02-1.08; P<10(-4)) and 1.04 (95% CI: 0.98-1.10; P = 0.20) were found for the two variants respectively. Similar results were also observed using dominant or recessive genetic model. There was strong evidence of heterogeneity, which largely disappeared after stratification by ethnicity. Significant results were found in Caucasians when stratified by ethnicity; while no significant associations were observed in East Asians and South Asians. Besides, we found that the rs10830963 polymorphism is a risk factor associated with increased impaired glucose regulation susceptibility. CONCLUSIONS: This meta-analysis demonstrated that the rs10830963 polymorphism is a risk factor for developing impaired glucose regulation and T2D.